Driver-passenger collaboration as a basis for human-machine interface design for vehicle navigation systems. Issue 3 (4th March 2017) - Antrobus, Vicki; Burnett, Gary; Krehl, Claudia
Abstract: Human Factors concerns exist with vehicle navigation systems, particularly relating to the effects of current Human-Machine Interfaces (HMIs) on driver disengagement from the environment. A road study was conducted aiming to provide initial input for the development of intelligent HMIs for in-vehicle systems, using the traditional collaborative navigation relationship between the driver and passenger to inform future design. Sixteen drivers navigated a predefined route in the city of Coventry, UK with the assistance of an existing vehicle navigation system (SatNav), whereas a further 16 followed the navigational prompts of a passenger who had been trained along the same route. Results found that there were no significant differences in the number of navigational errors made on route for the two different methods. However, drivers utilising a collaborative navigation approach had significantly better landmark and route knowledge than their SatNav counterparts. Analysis of individual collaborative transcripts revealed the large individual differences in descriptor use by passengers and reference to environmental landmarks, illustrating the potential for the replacement of distance descriptors in vehicle navigation systems. Results are discussed in the context of future HMIs modelled on a collaborative navigation relationship. Practitioner Summary: Current navigation systems have been associated with driver environmental disengagement, this study uses an on-road approach to look at how the driver–passenger collaborative relationship and dialogue can inform future navigation HMI design. Drivers navigating with passenger assistance demonstrated enhanced landmark and route knowledge over drivers navigating with a SatNav.